Problems of creation and functioning clusters associations - D. V. Skvirya (Путеводитель предпринимателя)
In the article problems and experience of creation and functioning of industrial clusters are considered. The special conditions, characteristic competitive advantages therefore the measures undertaken for creation of a cluster have to consider these conditions are inherent in each region. Depending on number of participants in most cases control of a cluster is exercised by the management company (MC) which is the specialized organization of operational management, the carrying-out expert and analytical, organizational, methodical and information maintenance.